P-119 The transition of patients from curative to palliative care: A systematic review of ethical issues. (1st September 2015) - Droste, Sigrid; Lysdahl, K Bakke; Hofmann, B
Abstract : Background: Transitions in end-of life care are frequent and burdensome for patients, families and professionals. This is particularly so for transitions from curative to palliative care as these pass from a treatment model to a care model. However, ethical issues, patients' preferences, values in transitions to palliative care are seldom addressed by ethicists. Aim: To systematically review the relevant ethical issues concerning transitions from curative to palliative care. Methods: We conducted: a) comprehensive systematic literature search (2013), update cluster search (2015), b) screening of retrieved records (predefined inclusion/exclusion criteria), c) extracting and quality assessment of relevant arguments, d) assembling to ethics domains (Hofmanns' question list on ethical issues in health technologies), e) synthesis of results. Results: Less than 50 relevant publications were identified, including a few qualitative studies and review articles. Ethical analyses were done by applying the methods of virtue ethics, casuistry and principles ethics. The publication authors identified areas complicating the transition: the nature of the process, the timing and the lack of information. Ethical issues are assigned to all these areas, including aspects (assessment/respect) of autonomy, beneficence, justice, under-/overtreatment. Patients have to abandon hope for cure and to face the impending death. Lack of time in decision-making, and inadequate information/communication on palliative care are identified risks to non-respect patients' preferences/values. Conclusion: Although few publications on transition to palliative care exist, many relevant ethical issues were addressed by them. To contribute to a best possible end-of-life care respecting patients' autonomy, dignity and preferences these issues should be transferred and integrated into the communications and shared decision-making on ACP.